Distributed Adaptive Dynamic Event-Triggered Control for Multiple Quadrotors - Wang, Hao; Shan, Jinjun (IEEE/ASME transactions on mechatronics, 2023)
This article studies formation control problems for leader-follower multiquadrotor systems subject to unknown perturbations and limited resources via an event-triggered mechanism. A distributed adaptive dynamic event-triggered formation control protocol is designed by utilizing a sliding-mode control approach, such that the integral sliding-mode manifold can be reached in finite time for the states of the nonlinear, coupled, and underactuated system with unknown external disturbances. A distributed integral sliding-mode surface is proposed to guarantee the formation tracking performance as the state trajectories of multiquadrotor systems move on the constructed sliding manifold. Then, a novel adaptive dynamic triggering strategy is developed to adjust the triggering interval dynamically and, thus, reduce the unnecessary resource consumption. Via the Lyapunov stability theory and the Barbalat lemma, sufficient conditions to ensure the formation tracking results are derived for leader-follower multiquadrotor systems. Simulations and experiments to validate the effectiveness of the proposed control scheme are conducted.